2011
DOI: 10.4028/www.scientific.net/amr.189-193.575
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of LaNi<sub>5</sub> by FFC Cambridge Process

Abstract: A new technique was proposed for preparation of LaNi5 powder by direct electrolytic deoxidation of solid La2O3–NiO mixture oxides in molten CaCl2–NaCl. Oxides pellets was sintered and used as cathode. High – density graphite was used as anode. Electrolysis was performed. Current change during electrolysis was recorded. XRD was used to analyse the composition of products. SEM was used to analysis surface and cross section of pellets before sintering, after sintering and after electrolysis. The preparation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It was claimed that the formation of the metallic phase is possible at 2.5 V in eutectic NaCl–CaCl 2 , with the reduction pathway initiated by metallising NiO to Ni, which then reacts with CeOCl to produce CeNi 5 . Zaho et al reported the preparation of CeNi 5 and LaNi 5 under 3.2 V in molten CaCl 2 at 1023 K. Zhang et al, prepared La 0.5 Ce 0.5 Ni 5 using the same conditions and electrolyte. Song et alused eutectic KCl–LiCl to produce CeNi 4 Cu alloy powders by electro-deoxidation of oxide precursors at 923 K. At such low temperature, no CeOCl was detected as an intermediate phase .…”
Section: Electro-deoxidation Under Controlled Voltage or Potentialmentioning
confidence: 99%
“…It was claimed that the formation of the metallic phase is possible at 2.5 V in eutectic NaCl–CaCl 2 , with the reduction pathway initiated by metallising NiO to Ni, which then reacts with CeOCl to produce CeNi 5 . Zaho et al reported the preparation of CeNi 5 and LaNi 5 under 3.2 V in molten CaCl 2 at 1023 K. Zhang et al, prepared La 0.5 Ce 0.5 Ni 5 using the same conditions and electrolyte. Song et alused eutectic KCl–LiCl to produce CeNi 4 Cu alloy powders by electro-deoxidation of oxide precursors at 923 K. At such low temperature, no CeOCl was detected as an intermediate phase .…”
Section: Electro-deoxidation Under Controlled Voltage or Potentialmentioning
confidence: 99%
“…The AB 2 's seem to be more sensitive to gaseous impurities than the AB 5 's [7] hence the advantage of LaNi 5 intermetallic compound is that they exhibit low hysteresis, are moderate to gaseous impurities and are effortlessly hydrogenated in the initial cycle after manufacture [8]. Conventionally, the metal hydride materials have been prepared by arc melting [9][10][11] , induction melting [12], mechanical alloying [8,[13][14][15] electro chemical synthesis [16,17], solid state reduction method [18].The preparation of Rare Earth metals and alloys production from its ores has not yet full-fledged in India .Therefore the production processes of Rare Earth based functional materials are found to be considered as a insightful area of research. The Reduction-Diffusion (R-D) process involves reduction of cheaper raw materials such as lanthanum oxide (La 2 O 3 ) by calcium and simultaneous diffusion in nickel [19][20][21] forming the intermetallic compound.…”
Section: Introductionmentioning
confidence: 99%